Optimisation of laser driven proton beams by an innovative target scheme. (22nd June 2017) - Ahmed, H.; Kar, S.; Cantono, G.; Doria, D.; Giesecke, A.L.; Gwynne, D.; Lewis, C.L.S.; Macchi, A.; Nersisyan, G.; Naughton, K.; Willi, O.; Borghesi, M.
Abstract: Proton beams driven by the target normal sheath acceleration mechanism exhibit large divergence and a broad energy distribution with low particle number at high energy. Such undesirable characteristics of the beam can be controlled and optimised by employing a recently developed helical coil technique, which exploits the transient self-charging of solid targets irradiated by intense laser pulses. Highly chromatic focusing of the broadband proton beams was achieved by employing this technique at the TARANIS laser system, where the selected energy slice was tuned by varying the pitch of the coil. A quasi-collimated, narrow energy band proton beam of ∼ 10 7 particles at 10 MeV was achieved, through a combination of focussing, energy selection and in-situ post-acceleration. This technique may provide a platform for a generation of compact, all-optical ion accelerators.